Clinical Risk Factors for Proliferative Vitreoretinopathy-I - Khan, Sanaullah Jan, Muhammad Daud Khan, Muhammad Kamran Khalid, Sardar Bahadar (Pakistan Journal of Ophthalmology, 2007)
Purpose: To evaluate clinical variables as risk factors for proliferative vitreoretinopthy (PVR). Materials & Methods: This cross-sectional comparative study was conducted at Khyber Institute of Ophthalmic Medical Sciences (KIOMS), Hayatabad Medical Complex (HMC), Peshawar from 1st August 2002 to 31st Dec 2002. Fifty patients of rhegmato-genous retinal detachment (RRD) were included randomly in our study. They were evaluated for the presence of both risk factors & PVR grading. Chi-square test was used to measure the difference in exposure rates & odds ratio was calculated to estimate the strength of association between risk factors & outcome. Results: Duration of retinal detachment (RD)>1month (p<0.05) was found to be statistically significant risk factor for PVR grade C or more. The exposure rates in closed globe injury, aphakia & pseudophakia and peripheral retinal degenerations were statistically not significant (p>0.1). None of the patients was giving a family history of RD so this variable was out of comparison procedure. Conclusion: Duration of RD >1 month is associated with high risk of high grade PVR, so this factor should be considered as important prognostic factor in the management of RRD.